Pengaruh Kualitas Produk dan Promosi Penjualan Terhadap Keputusan Pembelian Mascara Oriflame (Studi Pada Konsumen Mascara Oriflame Wilayah Surabaya Pusat) - NUR MASLAKHAH, ARINDA; LESTARI ANDJARWATI, ANIK (Jurnal Ilmu Manajemen (JIM), 2018)
The purpose of this study is to examine and analyze the effect of product quality and sales promtion on purchase decision mascara Oriflame. This research is a causality research with quantitative approach. Technique of sampling using non probability sampling with amount 110 respondents at offline store Oriflame Surabaya Center. Statistical analysis in this study is multiple linier regresiom with the help ofSPSS 22.0 software. The results of this study explain that product quality had a positive and significant effect on the purchasing decision, and sales promotion had a positive and significant effect on the purchasing decision.